2022
DOI: 10.48550/arxiv.2202.12841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lower limit for Newtonian-noise models of the Einstein Telescope

Abstract: The Einstein Telescope (ET) is a proposed third-generation gravitationalwave (GW) underground observatory. It will have greatly increased sensitivity compared to current GW detectors, and it is designed to extend the observation band down to a few Hz. At these frequencies, a major limitation of the ET sensitivity is predicted to be due to gravitational fluctuations produced by the environment, most importantly by the seismic field, which give rise to the so-called Newtonian noise (NN). Accurate models of ET NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…with S ξz the PSD, or in our case the CSD, of the vertical displacement of the Rayleigh wave and ρ 0,Surface = 2 800kg m −3 the surface density [46]. γ is a factor given by the elastic properties of the half space that takes into account the partial cancellation of the NN given by the compression/decompression of the rocks caused by the Rayleigh waves below the surface: we assume γ = 0.8 (see Fig 10 of [39]).…”
Section: Nn From Rayleigh Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…with S ξz the PSD, or in our case the CSD, of the vertical displacement of the Rayleigh wave and ρ 0,Surface = 2 800kg m −3 the surface density [46]. γ is a factor given by the elastic properties of the half space that takes into account the partial cancellation of the NN given by the compression/decompression of the rocks caused by the Rayleigh waves below the surface: we assume γ = 0.8 (see Fig 10 of [39]).…”
Section: Nn From Rayleigh Wavesmentioning
confidence: 99%
“…Earlier work has studied the effect from seismic and Newtonian noise on the instantaneous sensitivity P ET (f ) [18,29,46]. It was found that seismic noise could be dominant up to ∼ 2 Hz-3 Hz rather than just below 2 Hz [18].…”
Section: Noise Projection -Formalismmentioning
confidence: 99%